Comparing the Sustainability of Biomass Fuel Supply Options for a Small Scale Gasification Project in Rural Uganda - Christensen, Stephen (My University, 2013)
Recent studies have shown the potential and economic viability of biomass gasification based systems for electricity generation in rural Uganda (e.g. Buchholz et al., 2010; Furtado, 2012). The implementation of these systems hinges on the sustainability of fuel supply. A growing population using biomass for over 90% of their primary energy needs and land use change from forests being cut for small scale farming and large monoculture has caused Uganda to lose over 1/3 of its forest cover over the last two decades. Implementing a biomass based electricity system can further contribute to these problems if the biomass fuel supply is not sustainably managed. Pamoja Cleantech AB is a startup company based in Stockholm which will soon implement a small scale (10 kW) biomass gasification pilot project in the Magala Village, Mityana district in rural Uganda. Pamoja recognizes the environmental issues involved in gasification projects in Uganda and wishes to move forward in implementing a sustainable biomass fuel supply. This thesis addresses the question of which biomass fuel supply option is the best and most sustainable option for this project and future small scale gasification projects. In this paper, a sustainability framework has been developed in order to quantitatively compare the reliability, costs, and environmental and social impacts of different biomass fuel options for each individual site of operation in order to assure a fully sustainable supply. First, the framework is presented along with details on its development from considerations of existing Criteria and Indicator (C&I) Frameworks and sustainable biomass standards. An explanation and justification is also given for the importance of each of the sustainability criteria. The best supply options available at a given site are then chosen and compared using the sustainability framework. Results show that the three investigated supply options, buying firewood from the local market, purchasing agriculture residues, and implementing agroforestry and/or woodlot systems, are comparable economically in terms of the final price range for an oven dried ton of biomass supplied. Implementing outgrowing schemes, especially agroforestry systems, have significant advantages over the other two options in terms of potential social and environmental benefits. Although it is challenging to quantitatively measure reliability, we consider implementing agroforestry and woodlot systems to be a more reliable fuel supply option than purchasing firewood or agriculture residues. The recommended biomass supply for this project is using agriculture residues in the short term and local fuelwood as a backup while also implementing outgrowing schemes and growing trees locally in woodlot or agroforestry systems. This will increase the reliability of the fuel supply in the long term, as well as maximize local social and environmental benefits. Keywords: biomass,
Keywords: Mekanisk energiteknik; Energi; Hållbar utveckling; Mechanical energy engineering; Energy; Sustainable Development